Biomimetic Carbon Nanotube Films with Gradient Structure and Locally Tunable Mechanical Property. (31st October 2015) - Lin, Zhiqiang; Gui, Xuchun; Zeng, Zhiping; Liang, Binghao; Chen, Wenjun; Liu, Ming; Zhu, Yuan; Cao, Anyuan; Tang, Zikang
Abstract : Naturally existing materials often acquire unique functions by adopting a gradient structure with gradual change in their microstructure and related properties. Imparting such an elegant structural control into synthetic materials has been a grand challenge in the field. Here, the concept of gradient structure into macroscopic carbon nanotube (CNT) films is employed and the CNT arrangement from well‐aligned array to completely random distribution, in a continuous and smooth way, is changed. Gradient films with tailored aligned‐to‐random transition rate or multilevel hierarchical structures with repeated transition have been fabricated. Local deformation and mechanical properties are directly related to the arrangement of CNTs and can be tailored by Herman's orientation factor; in particular, the elastic modulus and stiffness span over several orders of magnitude from aligned to random regions within a single monolithic film. Controlled synthesis of macroscopic CNT gradient structures with tunable mechanical properties opens a potential route toward manufacturing biomimetic functional materials with locally optimized design. Abstract : A macroscopic carbon nanotube (CNT) film with gradient structure is synthesized by one‐step CVD. The CNT arrangement gradually changes from well aligned to random distribution in a continuous and smooth way along the thickness direction. Local deformation and mechanical properties such as stiffness and elastic modulus are determined by the Herman's orientation factor and span over three orders of magnitude.